Avaliação da inteligência de pacientes com fenilcetonúria atendidos peloPrograma de Triagem Neonatal de Minas Gerais - Isabel Pimenta Spinola Castro (2008)
Phenylketonuria (PKU) is an autosomal recessive diseaseaffecting 1/21,000 live births in the State of Minas Gerais. Early treatmentprevents the onset of clinical manifestations and irreversible damages inthe central nervous system. According to some studies, however, mildcognitive impairment can be found even in cases of early treatment.The aim of study was evaluate the intelligence among PKUpatients diagnosed and treated early by (who have been provided withearly treatment within) Minas Gerais State Newborn Screening Programand Support Diagnosis Center (School of Medicine, Federal University ofMinas Gerais). The sample includes 63 children who were submitted to WISC-III intelligence test (a standardized and validated test for the Brazilian population). All the subjects had their blood phenylalanine (phe) concentration analyzed in order to probe the association between intellectual performance and disease control. In addition, ordinal regression analyses determined the chances of children under proper dietary control having better intelligence test results compared to children under less accurate control.Were analysed the chances of children with best socio-economical levels present better intelligence performance when compared with children belong to low income families.The statistic test ANOVA was used. According to Total IQ parameters 58,7% of the patients have cognitive performance similar to the average performance, while 14% of the pacients were classified according to higher categorie higher and much higher and 27% was in a area of lower income borderline and disabled intellectually. A statistical association was found between the blood phe concentration, over treatment, and Total/ Accomplishment/Verbal IQs. Results also indicate better Verbal IQ performance compared to Accomplishment IQ performance. A statistical association was found between Total/Accomplishment/Verbal IQs and blood phe concentration for all age groups, except under-2-year-old children. The socio-economic assessment reveals that 69,9% of thefamilies belong to low income families, in the categories low lower andlow higher. Patients belonging to upper income groups presented 4,03 times more chances have superior or medium IQ compared to those belonging to lower income groups. The findings of this study reveals that, a PKU child, under more accurate controls of blood phenylalanine concentration, over treatment, 4,29 times mores chances to have better intelligence performance in WISC-III compared to children under worse controls.